Relationship between the length of the forefoot bones and performance in male sprinters - Tanaka, T.; Suga, T.; Ohtsuka, M.; Misaki, J.; Miyake, Y.; Kudo, S.; Nagano, A.; Isaka, T. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Although recent studies have reported that the forefoot bones are longer in sprinters than in non-sprinters, these reports included a relatively small number of subjects. Moreover, while computer simulation suggested that longer forefoot bones may contribute to higher sprint performance by enhancing plantar flexor moment during sprinting, the correlation between forefoot bone length and sprint performance in humans has not been confirmed in observational studies. Thus, using a relatively large sample, we compared the length of the forefoot bones between sprinters and non-sprinters. We also examined the relationship between forefoot bone length and performance in sprinters. The length of forefoot bones of the big and second toes in 36 well-trained male sprinters and 36 male non-sprinters were measured using magnetic resonance imaging. The length of forefoot bones in the big and second toes was significantly longer in sprinters than in non-sprinters. After dividing the sprinters into faster and slower groups according to their personal best time in the 100-m sprint, it was found that the forefoot bone length of the second toe, but not that of the big toe, was significantly longer in faster group than in slower group. Furthermore, the forefoot bone length of the second toe correlated significantly with the personal best time in the 100-m sprint. The present study supported evidence that the forefoot bones are longer in sprinters than in non-sprinters. In addition, this is the first study to show that longer forefoot bones may be advantageous for achieving superior sprint performance in humans.